Rumensin for the lactating dairy cow - J.C. Kube; R.A. Frey; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1987)
Two Holstein cows were fed Rumensin for 12 weeks, beginning approximately 90 days postpartum. Milk production increased 7%, whereas percentage fat in milk decreased 10.3%. Percentage protein in milk increased 9.6% in the early stages and decreased 10.2% in the late stages of the study. Daily fat yield did not change, whereas protein yield increased in the early stages, but did not change in later stages. Fat corrected milk (FCM) did not change with treatment, but dry matter intake (DMI) tended to increase when Rumensin was fed. Acetate concentration did not change whereas propionate concentration increased, causing a significant decrease in ruminal acetate:propionate ratio. Rumen pH showed a nonsignificant numerical increase.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Rumensin; Milk production; Propionate